Recent advances in recombinase polymerase amplification: Principle, advantages, disadvantages and applications - Tan, Meiying; Liao, Chuan; Liang, Lina; Yi, Xueli; Zhou, Zihan; Wei, Guijiang (Frontiers in Cellular and Infection Microbiology, 2022)
After the outbreak of SARS-CoV-2, nucleic acid testing quickly entered people’s lives. In addition to the polymerase chain reaction (PCR) which was commonly used in nucleic acid testing, isothermal amplification methods were also important nucleic acid testing methods. Among several common isothermal amplification methods like displaced amplification, rolling circle amplification, and so on, recombinase polymerase amplification (RPA) was recently paid more attention to. It had the advantages like a simple operation, fast amplification speed, and reaction at 37-42°C, et al. So it was very suitable for field detection. However, there were still some disadvantages to RPA. Herein, our review mainly summarized the principle, advantages, and disadvantages of RPA. The specific applications of RPA in bacterial detection, fungi detection, virus detection, parasite detection, drug resistance gene detection, genetically modified food detection, and SARS-CoV-2 detection were also described. It was hoped that the latest research progress on RPA could be better delivered to the readers who were interested in RPA.